Impact of the COVID-19 pandemic on the Belt and Road Initiative (The Journal of Psychology and Sociology, 2021)
This article analyzes the implementation of the Belt and Road Initiative in Central Asian countries during the COVID-19 pandemic. In 2020, the whole world has to develop in the face of the COVID-19 pandemic. In addition, downfall in economic growth a recession in the global economy, which led to a slowdown and recession in economic growth, suspension of production, closure of borders, and it was China that was the first to face this problem. All this negatively affected the projects of the One Belt, One Road initiative. The purpose of the study was to identify how the COVID-19 pandemic influenced the Belt and Road Initiative and what measures China has taken to preserve BRI projects, and how the Health Silk Road project has become a lifeline for China. It also discusses why OBOR projects in Central Asia are strategically important for China. The article presents an analysis of the economic, social and political problem of the initiative during the COVID-19 pandemic. The article shows the results of the survey analysis, indicating that the impact of the COVID-19 pandemic on the initiative is short-term. The practical significance of the study lies in the fact that at the moment there are so many studies examining the impact of the COVID-19 pandemic on the Belt and Road Initiative in Central Asia and this article will supplement the literature.Key words: Belt and Road Initiative, China, COVID-19 pandemic, Central Asia.